Analisis kinerja keuangan rumah sakit umum daerah a.w. sjahranie samarinda sebelum dan sesudah implementasi badan layanan umum - Lipan Sonya Alvionita; Yunus Tete Konde; Indra Suyoto Kurniawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this study is to analyze the growth rate of financial performance that occurred in 2010 to 2015 at the Abdul Wahab Sjahranie Hospital. Analytical tools used in this research is the Director General of the Treasury Regulation Number PER-36/PB/2012 assessment guidelines of the financial performance of the Agency’s Public Service Work Unit. From the analysis and discussions in mind that in 2010 to 2015 which was the year after the published guidelines decline while the total score of 1,4 in 2010 to 2011 there was no increase or decrease or can be said to have a fixed total score. Despite the decline occurred in the year after the published guidelines published from a year before, some of the financial ratios in the year after the issue has increased compared to the year before the published guidelines. Based on these results, it is suggested the hospital Abdul Wahab Sjahranie can perform analysis of the overall financial performance and routine, because financial performance analysis can assess or measure the condition of the hospitals’s financial performance, which is the goal that hospitals can know the state of the strenghts and weaknesses of existing to be used as a guide in determining policies on short-term work programs and long-term hospitals in the next period is expected to be more focused as needed service to the community.